HUBUNGAN BUDAYA INDIVIDUALIS-KOLEKTIF DAN MOTIVASI BERBELANJA HEDONIK PADA MASYARAKAT KOTA JAKARTA - Devi Jatmika (Psibernetika, 2017)
Many shopping centers try to create an environment that makes consumers feel comfortable when they do shopping. Hedonic shopping motivation relates to contentment and enjoyment by shopping experience, it creates happiness feeling. Hedonic shopping motivation can not be separated from the role of culture in the society. This research aimed to know the relationship between individualist-collective culture with hedonic shopping motivation among people in Jakarta. The research used non ecperimental quantitative research. The data was collected by distributing hedonic shopping motivation and individualist-collective culture questionnaire. Total respondents in this research were 134 people. The results revealed collective culture (mean= 18.33) has higher mean rather than individualist culture (mean= 17.29). Statistic analysis with Spearman Coorelation, r= 0.187 ad p= 0.031 < 0.05. Meanwhile, individualistic culture showed no coorelation with hedonic shopping motivation, r= 0.164 and p= 0.059 >0.05. Collective culture also had significant relationship with role shopping (r= 0.241, p= 0.005), social shopping (r=0.179, p= 0.038) and value shopping (r= 0.241, p= 0.042). The research concluded people in Jakarta tend to have collective culture. There was a relationsip between collective culture and hedonic shopping motivation, especially role shopping, social shopping dan value shopping. Keywords: Hedonic Shopping Motivation, Culture, Collective Culture, Individualistic Culture